Doktrin Roh Kudus (Pneumatologi) - Arestu Yulanda; Brando Frans Willi Malau; Cindi Anisa Bahar; Sarmauli Sarmauli (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
The doctrine of the Holy Spirit or Pneumatology, is an important teaching in Christianity related to the role, work and presence of the Holy Spirit in the lives of believers. The Holy Spirit, as the third Person of the Triune God, plays an active role in providing spiritual gifts, strengthening faith, and enabling the congregation to live according to God’s will. This article uses a literature study method to explore theological views about the Holy Spirit from the Bible, theological interpretation, and historical studies. The purpose of this article is to provide a deeper understanding of the role of the Holy Spirit in the spiritual life of Christians and its essence in everyday life.